2018
DOI: 10.1101/249912
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The frontal aslant tract (FAT) and its role in speech, language and executive function

Abstract: In this review, we examine the structural connectivity of a recently-identified fiber pathway, the frontal aslant tract (FAT), and explore its function. We first review structural connectivity studies using tract-tracing methods in non-human primates, and diffusion-weighted imaging and electrotimulation in humans. These studies suggest a monosynaptic connection exists between the lateral inferior frontal gyrus and the pre-supplementary and supplementary motor areas of the medial superior frontal gyrus. This co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 181 publications
2
48
0
Order By: Relevance
“…There is some evidence that the right hemisphere FAT may support the initiation and control of motor movements generally, as damage to the right FAT can result in Foix-Chavany-Marie syndrome, an impairment of voluntary control of certain facial and pharyngeal movements (e.g., laughing, coughing) with intact reflexes in the same muscles (Martino et al, 2012;Brandao et al, 2013). These impairments have not been observed after damage to the left FAT, which may support a dissociation between the left and right hemisphere FAT (Dick et al, 2018). It is important to emphasize that while we have framed the SCOPE hypothesis as applying to sentence production, there is nothing in our data that precludes a role for the FAT in relating other hierarchically organized action sequences to planning processes necessary for their production.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…There is some evidence that the right hemisphere FAT may support the initiation and control of motor movements generally, as damage to the right FAT can result in Foix-Chavany-Marie syndrome, an impairment of voluntary control of certain facial and pharyngeal movements (e.g., laughing, coughing) with intact reflexes in the same muscles (Martino et al, 2012;Brandao et al, 2013). These impairments have not been observed after damage to the left FAT, which may support a dissociation between the left and right hemisphere FAT (Dick et al, 2018). It is important to emphasize that while we have framed the SCOPE hypothesis as applying to sentence production, there is nothing in our data that precludes a role for the FAT in relating other hierarchically organized action sequences to planning processes necessary for their production.…”
Section: Discussionmentioning
confidence: 45%
“…If the IFG is composed of functionally distinct sub-regions, then it is important to consider if the FAT consists of functionally dissociable tracts with different endpoints in different subregions of the of IFG. Pars opercularis and pars triangularis are the regions of the IFG most commonly described as the endpoints of the FAT (Dick et al, 2018), and an important open question is whether there may be different subcomponents of the FAT, projecting to different regions of the IFG, that support different functions.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of these regions in language processing has been previously noted, although not consistently (Price, ). It is not surprising that these regions were mapped using functional connectivity, considering the strong underlying structural connectivity between these dorsal regions and the inferior frontal gyrus via the frontal aslant tract (Catani et al, ; Dick, Garic, Graziano, & Tremblay, ). Still, these regions showed moderate to no involvement in our task.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible interpretation comes from the possibility that premotor cortices possess superordinate properties (Schubotz and von Cramon, 2001;Schubotz, von Cramon and Lohmann, 2003;Schubotz et al, 2010). In Shubotz and colleagues' studies, the premotor activations were found to systematically represent information in different domains (time, space, objects) in various non-motor visual (Schubotz and von Cramon, 2001) and auditory (Schubotz, von Cramon and Lohmann, 2003) The SMA is involved in both speech perception and production (Hertrich, Dietrich and Ackermann, 2016;Lima, Krishnan and Scott, 2016), and in reading and writing (Price, 2010;Planton et al, 2013;Longcamp et al, 2014),and appears to be connected to the lateral inferior frontal gyrus through the Frontal Aslant Tract (Dick et al, 2019). During speaking, it is usually thought to participate in the initiation of speech motor programs, internally specified action selection, inhibition and in higher superordinate planning functions (Alario et al, 2006;Tremblay and Gracco;2006;Peeva et al, 2010;Tourville and Guenther, 2011).…”
Section: Shared Neural Substrates In the Left And Medial Frontal Cortexmentioning
confidence: 99%